The species evenness of "prey" bacteria correlated with Bdellovibrio-and-like-organisms (BALOs) in the microbial network supports the biomass of BALOs in a paddy soil. Issue 12 (25th September 2020) - Qian, Hang; Hou, Chunli; Liao, Hao; Wang, Li; Han, Shun; Peng, Shaobing; Chen, Wenli; Huang, Qiaoyun; Luo, Xuesong
ABSTRACT: To seek how soil biotic and abiotic factors which might shape the Bdellovibrio -and-like-organisms community, we sampled paddy soils under different fertilization treatments including fertilization without nitrogen (Control), the nitrogen use treatment (N) and the nitrogen overuse one (HNK) at three rice growing stages. The abundances of BALOs were impacted by the rice-growing stages but not the fertilization treatments. The abundances of Bdellovibrionaceae -like were positively associated with soil moisture, which showed a negative relationship with Bacteriovoracaceae -like bacteria. High-throughput sequencing analysis of the whole bacterial community revealed that the α-diversity of BALOs was not correlated with any soil properties data. Network analysis detected eight families directly linked to BALOs, namely, Pseudomonadaceae, Peptostreptococcaceae, Flavobacteriaceae, Sediment-4, Verrucomicrobiaceae, OM27, Solirubrobacteraceae and Roseiflexaceae . The richness and composition of OTUs in the eight families were correlated with different soil properties, while the evenness of them had a positive effect on the predicted BALO biomass. These results highlighted that the bottom-up control of BALOs in paddy soil at least partially relied on the changes of soil water content and the diversity of bacteria directly linked to BALOs in the microbial network. Abstract : The variation of BALOs in paddy soil was shaped by the changes of soil water content and the diversity of bacteria directly linked to BALOs in the microbial network.